Mapping LGPD Principles to Ethical Principles in the Context of Artificial Intelligence - Braz, Ana Caroline da Rocha; Canedo, Edna Dias (Anais do Workshop sobre as Implicações da Computação na Sociedade (WICS); 2025: Anais do VI Workshop sobre as Implicações da Computação na SociedadeDO - 10.5753/wics.2025.7160, 2025)
The intersection between the ethical principles of the Brazilian General Data Protection Law (LGPD) and Artificial Intelligence (AI) presents a significant challenge in regulating data usage and addressing ethical risks. This study investigates the compatibility between these principles by identifying their points of convergence and divergence, as well as the practical challenges involved in their application. The research draws on a combination of literature review, document analysis, and a survey exploring participants’ perceptions of key issues such as transparency, security, accountability, and privacy. Findings reveal a strong alignment between the LGPD’s principles and the ethical values underlying AI. However, important challenges remain, including the absence of specific AI regulation, difficulties related to algorithmic explainability, and uncertainty regarding accountability. The study underscores the urgent need for more robust technical and regulatory frameworks to ensure the responsible development and deployment of AI systems that uphold individuals’ fundamental rights.